What do men want? A review of the barriers and motivators that engage older men in physical activity. (12th November 2020) - Blankley, Joshua; Ferreira Martins Garcia, Victoria; McCurran, Patrick; San Luis, Eunice; Wang, Caroline Yimeng; Calder, Allyson; Baxter, G. David
Abstract: Background: Physical activity (PA) is a primary and secondary strategy used to reduce the risk of non-communicable diseases, whilst reducing the risk of morbidities. Approximately 71% of deaths that occurred in 2016 worldwide were due to non-communicable diseases. For men, many of these deaths could be prevented through lifestyle changes such as increasing physical activity; however, most older men struggle to complete the recommended 150 min/week of physical activity. Objective: This review aimed to investigate the barriers that prevent older men from engaging in physical activity, and what factors (or facilitators) encourage them to participate. Method: A systematic search was conducted across nine databases for papers published between 2010 and 2020. Studies were screened for eligibility and quality-assessed, data were extracted, and themes identified. Major findings: A total of 7 qualitative studies, one cross-sectional study and one randomized controlled trial, were included in the review; this included a total of 921 male participants aged above 60 years old. Barriers and motivating factors were categorized as follows: personal, environmental, and exercise tasks. Older men were commonly motivated to exercise to preserve meaningfulness in their lives, for accomplishment, and to maintain physical and mental health. The common barriers identified by older men included: unmotivating attitudes from their social environment, fear of injury, and lack of appropriate opportunities. Conclusion: Men are more likely to engage in PA if it is meaningful, preserves or improves physical function, and strengthens their social relationships. These findings provide insights about strategies to engage older men in physical activity, and thus improve their quality of life.